Draft genome sequence data of Urechis unicinctus, a marine echiuroid worm - Xudong Jiao; Jiaxin Shi; Song Qin; Donghui Zhao; Yinchu Wang (Data in Brief, 2021)
Urechis unicinctus is mainly distributed in Japan, north Korea and the Yellow Sea and the coast of Bohai Bay in China, and its nutrition is rich. The body of Urechis unicinctus contains many types of bioactive polypeptides, such as plasmin and tachykinin, which hold high economic and medicinal values. Therefore, the study of Urechis unicinctus has great significance. But the genome of Urechis unicinctus remains unavailable till now. To further understand the evolution of Urechis unicinctus and determine more effective application of it, we assembled the first draft genome sequence and the assembly of Urechis unicinctus. The dataset can be assessed from the BioProject at NCBI (https://www.ncbi.nlm.nih.gov/bioproject/?term=Urechis unicinctus).